1909. Do Infectious Disease Services Save Money? Accounting Analysis Before and After Introduction of a New Clinical Infectious Disease Service at a Tertiary Hospital in New Zealand. (26th November 2018) - Huggan, Paul; Shirley, Sarah; Kunac, Tracey; Mills, Graham
Abstract: Background: Infectious disease and antimicrobial stewardship services are generally held to be cost-saving in large healthcare facilities. Actual comparisons comparing costs before and after implementation of a clinical infectious disease (CID) service are lacking. Methods: Our 600+ bed tertiary hospital funded a CID service in 2015. Prior to this, CID expertise was largely provided by telephone consultation to a microbiologist and/or a part-time CID specialist with no nursing, pharmacy or resident medical officer (RMO) support. Out-patient IV antibiotics (OPIVA) were provided at the discretion of individual clinicians. The new CID team introduced an in-patient consult and OPIVA service. A management accounting analysis was undertaken to compare the total costs of care for patients admitted to OPIVA in financial years (FY) 2011 and 2012 (FY11/12) and 2016 (FY16). Short courses of out-patient therapy for cellulitis were excluded during both periods. Results: In FY11/12 and FY16, 144 and 145 patients were discharged to OPIVA. 51 of 191 patients (27%) with CID consults for suspected or proven bacterial infection were admitted to OPIVA in 2016. Age, sex, and diagnosis were similar in both groups. Ceftriaxone and glycopeptide use increased in the 2016 cohort. Drug-related adverse events were more common in 2016 whilst line complications did not change. There were two unexpected OPIVA deaths in FY11/12 and none in FY16. Reduced in-patient bed-days in 2016 saved NZD 1.45 million, with an additional NZD 157, 000 saving in total drug costs. This represented a 276% return on investment against wage costs for the CID team. Conclusion: In our hospital, a CID team significantly reduced bed-days and drug costs for common infectious diseases. Disclosures: All authors: No reported disclosures.